Arginase in Parasitic Infections: Macrophage Activation, Immunosuppression, and Intracellular Signals - Stempin, Cinthia (2010)
A type 1 cytokine-dependent proinflammatory response inducing classically activated macrophages (CaMvarphis) is crucial for parasite control during protozoan infections but can also contribute to the development of immunopathological disease symptoms. Type 2 cytokines such as IL-4 and IL-13 antagonize CaMvarphis inducing alternatively activated macrophages (AaMvarphis) that upregulate arginase-1 expression. During several infections, induction of arginase-1-macrophages was showed to have a detrimental role by limiting CaMvarphi-dependent parasite clearance and promoting parasite proliferation. Additionally, the role of arginase-1 in T cell suppression has been explored recently. Arginase-1 can also be induced by IL-10 and transforming growth factor-beta (TGF-beta) or even directly by parasites or parasite components. Therefore, generation of alternative activation states of macrophages could limit collateral tissue damage because of excessive type 1 inflammation. However, they affect disease outcome by promoting parasite survival and proliferation. Thus, modulation of macrophage activation may be instrumental in allowing parasite persistence and long-term host survival.